DISTRIBUSI LONGITUDINAL BERBAGAI SPESIES IKAN DI SUNGAI DAMAR KABUPATEN KENDAL (Life Science, 2013)
Damar River receives waste inputs from household industrial activity and agricultural activity that can effect on the distribution and the diversity of living things in it, including the fish. This research is exploration research, with the sampling was conducted at 5 stations in different locations. The samples were collected at 3 different sampling times with 2-week interval. Data was analysed using longitudinal distribution, based on the density of species per-station and per-period of sampling. The species diversity was also calculated using Shanon Diversity Index. There were 10 fish species that were distributed in the Damar River i.e. Anabas testudineus, Trichogaster trichopterus, Clarias batracus, Oreochormis niloticus, Arius caelatus, Periophtalmus malacensis, Scatophagus argus, Crenimugil heterocheilos, Pomadasys argenteus, and Sillago robusta. Species which was distributed along the Damar River was Anabas testudineus with the distribution center at river estuary. The Diversity Index value of Damar River is categorized as intermediate (1.88), thus it shows that the water quality criteria of Damar River is lightly polluted water.